The effect of education on economic growth in Greece over the 1981–2009 period. Does the proxy of human capital affect the estimation?. (1st January 2012) - Tsamadias, Constantinos; Pegkas, Panagiotis
This study examines the effect of education on economic growth in Greece, during the period 1981 to 2009, by applying the model introduced by Mankiw et al. (1992). Three different proxies of human capital were used, school enrolment rates in secondary education, average years of schooling and the proportion of the labour force which has received secondary education. The empirical analysis reveals that education has had a negative effect on economic growth. Specifically, the coefficients for the three proxies that were used have resulted in negative sign but only for the enrolments rates case was statistically significant. The model explained 26% up to 34% of the variation of the economic growth rate through the variation of the independent variables in different cases.